Assessment of dietary patterns in obese children and adolescents at risk of pre-diabetes in Basra/Iraq - Abbas S. Musher,; Majid A. Maatook,; Dhaigham I. Atwan, (University of Thi-Qar Journal of Science, 2023)
the role of nutrition in developing pre-diabetes among obese children and adolescents remains a major problem. Method: A cross-sectional study based on food frequency questionnaire data was conducted on obese children and adolescents aged 6